A Perspective on Extreme Open Science: Companies Sharing Compounds without Restriction. (June 2019) - Drewry, David H.; Wells, Carrow I.; Zuercher, William J.; Willson, Timothy M.
Although the human genome provides the blueprint for life, most of the proteins it encodes remain poorly studied. This perspective describes how one group of scientists, in seeking new targets for drug discovery, used open science through unrestricted sharing of small molecules to shed light on dark matter of the genome. Starting initially with a single pharmaceutical company before expanding to multiple companies, a precedent was established for sharing published kinase inhibitors as chemical tools. The integration of open science and kinase chemogenomics has supported the study of many new potential drug targets by the scientific community.